Some approaches to a quantitative measure of the stability of dynamical systems - Kutsenko, Alexander; Kovalenko, Sergey (L. N.Gumilyov Eurasian National University, 2019)
The article analyses the state of the problem of the quantitative measure of the stability of dynamic systems. Two approaches to solve this problem are proposed. The first approach is based on the study of the deformation process of an arbitrary region of the phase space on the solutions of systems of differential equations. The second method is based on a multiple assessment of the integral quadratic functionals of the trajectories of a stable dynamical system
Keywords: dynamic system; stability; integral quadratic functional; Lyapunov matrix equation; technical stability; стійкість; технічна стійкість; інтегральний квадратичний функціонал; матричне рівняння Ляпунова; динамічні системи